Neutrophil Extracellular Traps in SARS-CoV2 Related Pneumonia in ICU Patients: The NETCOV2 Study - Godement, Mathieu; Zhu, Jaja; Cerf, Charles; Vieillard-Baron, Antoine; Maillon, Agathe; Zuber, Benjamin; Bardet, Valérie; Geri, Guillaume (Frontiers in Medicine, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a poorly understood disease involving a high inflammatory status. Neutrophil extracellular traps (NETs) have been described as a new pathway to contain infectious diseases but can also participate in the imbalance of the inflammatory and the coagulation systems. NETs could be a therapeutic target in COVID-19 patients. Methods: Consecutive patients with SARS-CoV2 related pneumonia admitted in intensive care unit were included in a prospective bicentric study. Neutrophil extracellular traps concentrations were quantified in blood samples at day-1 and day-3 by flow cytometry. The primary outcome was the association between the blood NETs quantification at ICU admission and the number of days with refractory hypoxemia defined by a PaO2/FiO2 ratio inferior than 100mmHg was assessed. Results: Among 181 patients admitted to the ICUs for acute respiratory failure related to SARS-CoV2 pneumonia, 58 were included in the analysis. Patients were 62 [54, 69] years old in median, mostly male (75.9%). The median number of days with severe hypoxemia (PaO2/FiO2 < 100mmHg) was 4 [2, 6] days and day-28 mortality was 27.6% (n=16). We observed a strong correlation between day-1 blood NETS level and blood levels of leucocytes at day-1 and day-2. The blood level of NETS was lower at day-1 than at day-3 in patients who died (32.6 [22.3, 70.3] vs. 56.7 [23.3, 105.6] p<0.001, 0.37 [0.0, 1.45] vs. 2.2 [0.0, 4.3] p<0.001 and 4 [1.2, 7.6] vs. 6.8 [1.8, 15.0] p<0.001 for MPO+, Cit-H3+ and double-positive NETS, respectively). In multivariable negative binomial regression, single positive MPO+ NETs were negatively associated with the number of days with severe hypoxemia within 7 days (0.84 [0.73, 0.97]), while neither single positive Cit-H3+ NETS nor double-positive NETS were significantly associated with the primary outcome. Conclusion: The blood level of NETs at day-1 was negatively associated with the number of days with severe hypoxemia in patients admitted to the intensive care unit for SARS-CoV2 related pneumonia. An increase of the blood level of NETs between day-1 and day-3 discriminated the patients who died within day-28.